Influence of vigabatrin on visual field and electrophysiological tests in patients with epilepsy - Mrugacz, Małgorzata; Bakunowicz-Łazarczyk, Alina (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
Vigabatrin (VGB) is a new antiepileptic drug, that acts by the irreversible inhibition of gamma-aminobutyric acid (GABA) aminotransferase. Chronic antiepileptic therapy with VGB is associated with visual field defects and electrophysiological changes.